Ultra-fast electro-reduction and activation of graphene for high energy density wearable supercapacitor asymmetrically designed with MXene - Karim, Golam Masud; Dutta, Pronoy; Majumdar, Abhisek; Patra, Amalika; Deb, Sujit Kumar; Das, Snehasish; Dambhare, Neha V.; Rath, Arup K.; Maiti, Uday Narayan (Carbon, 2023)
Controlled perforation of graphene is vital to surpass the performance of supercapacitors that rely on their pristine form. However, their practical utilization has been halted by energy-inefficient and lengthy processing. Here, we are reporting a pulse Joule heating strategy for on-site reduction and activation to realize a multimodal porous framework made of perforated graphene using millisecond current pulses. The multimodal porosity and surface functionalities of graphene were regulated at an ultrafast rate by passing a transient current. Asdeveloped ready-to-use electrode composed of nano-to-macro multimodal porosity displays high areal capacitance of 380.2 mF cm-2 in symmetric two-electrode configuration, which is nearly 1.6 times higher than the nonelectro activated counterpart. Furthermore, a high-performance wearable asymmetric supercapacitor with an areal energy density of 107.8 mu Wh cm-2 was realized using this multimodal porous graphene in combination with suitable negative electrodes made of MXene. High energy density, together with stable and repeatable performance of the wearable device for 10000 cycles of charge-discharge and 5000 cycles of bending, signifies the importance of the as-developed device for practical wearable applications. Direct, simple processing of electrodes and orders of magnitude lower cost-and-processing-time can make the process appealing for practical wearable and other energy storage applications.
Keywords: asymmetric supercapacitor; Graphene activation; Joule heating; Solid-state supercapacitor; Wearable device

Programmable tuning of graphitic order impacting the perforation of MOF-derived carbon nanostructures for all-purpose high-energy-density supercapacitors - Karim, Golam Masud; Patra, Amalika; Deb, Sujit Kumar; Das, Snehasish; Dutta, Pronoy; Mukherjee, Priyam; Bera, Pranab; Upadhya, Hemanta; V. Dambhare, Neha; Rath, Arup K.; Ghosh, Debasis; Maiti, Uday Narayan (Carbon, 2026)
Precise manipulation of graphitic order in carbon nanostructures and derived materials can be a key strategy to avail their full potential in multifunctional applications; however, it is incredibly challenging to implement on a practical scale. Here, we report a unique programmable pulsed Joule heating (PJH) strategy for the development of graphitization-tunable carbon nanoleaves (GNL) from a metal-organic framework (MOF) and for the precise recovery of graphitic order in GNL after it undergoes pore-forming surface oxidation. A unique electrochemical perforation (ECP) strategy is employed to unzip the graphitic layers of GNLs, thereby removing the in situgenerated fine metal nanoparticles. The adjustable graphitization of GNL by PJH, tunable perforation by ECP, and programmable conductivity recovery by PJH are highly effective in optimizing energy storage performance in supercapacitor devices. As-modified GNLs exhibit an areal capacitance as high as 290.7 mF cm- 2 in aqueous electrolytes, which is 434% higher than that of pristine GNLs. It is this unique combination of a highly accessible surface area, facilitated by ECP, and restored conductivity, achieved by PJH, that drives the exceptional performance boost compared to pristine GNL. The high conductivity and open porosity greatly improved the performance of the water-in-salt (WIS) electrolyte supercapacitor, delivering very high energy density (127.5 mu Wh cm- 2), an extended voltage window (2.3 V), and impressive capacity retention (89%) after 15000 chargedischarge cycles. These ready-to-use binder-free electrodes also exhibit excellent, highly stable performance in wearable asymmetric supercapacitor devices.
Keywords: Electrochemical perforation; Porous graphitic nanostructure; Ultrafast graphitization; Water-in-salt electrolyte; wearable supercapacitor